Government Health Expenditures and Economic Growth: A Feder-Ram Approach for the Case of Turkey - Kurt, Serdar (International Journal of Economics and Financial Issues, 2015)
This paper aims to test the direct and indirect (external) effects of health expenditures on economic growth using the Feder-Ram model. It uses aggregate and manufacturing industrial production as total output, total government health expenditures, general government cure and pharmaceutical products health expenditures, general government medicine and health expenditures series belonging to the economy of Turkey between the 2006:M01-2013:M10 period using seasonally adjusted and real monthly data. The results obtained from this study have shown that in general, the direct impact of government health expenditures on economic growth in Turkey is positive and significant and its indirect impact is negative and significant. Moreover, when the coefficient calculated for efficiency is considered, it can be argued that while there are not very significant differences between the government health sector and other sectors, the government health sector is slightly more efficient. In this case it can clearly be seen that there is a requirement to improve and further develop the health sector in Turkey. Keywords: Direct and Indirect Effects; Government Expenditure; Health Expenditures; Economic Growth and Development; the Feder-Ram Model. JEL Classifications: H23; H51; I15; O11; O41